Nature-inspired remodeling of (aza)indoles to meta-aminoaryl nicotinates for late-stage conjugation of vitamin B3 to (hetero)arylamines - Begur Vasanthkumar Varun (Nature Portfolio, 2020)
Vitamin B3 derivatives display a range of biological activities. Here, the authors report the synthesis of meta-aminoaryl nicotinates, derivatives of vitamin B3, and their late-stage conjugation with (hetero)arylamines, ultimately expanding the chemical space for biomedical research.